2009
DOI: 10.1111/j.1440-1754.2007.01254.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of intravenous maintenance fluids

Abstract: Aim: Traditional paediatric intravenous maintenance fluids are prescribed using hypotonic fluids and the weight-based 4:2:1 formula for administration rate. However, this may cause hyponatraemia in sick and post-operative children. We studied the effect of two types of intravenous maintenance fluid and two administration rates on plasma sodium concentration in intensive care patients. Methods: A Factorial-design, double-blind, randomised controlled trial was used. We randomised 50 children with normal electrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
94
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 44 publications
6
94
0
5
Order By: Relevance
“…One retrospective, informatics-enabled study demonstrated that undergoing a surgical procedure was an independent risk factor for hospital-acquired hyponatremia [adjusted odds ratio (OR) 1.44, 95 % confidence interval (CI) 1.09-1.91]; this effect was similar to that attributed to fluid hypotonicity (adjusted OR 1.37, 95 % CI 1.03-1.84) [7]. A randomized controlled trial comparing 0.9 % saline and 0.18 % saline in a PICU population demonstrated that plasma sodium tended to decrease more in surgical patients than medical patients (-2.3 mmol/L; 95 % CI −0.46 to 0.1, P=0.057) [12].…”
Section: Postoperative Hyponatremiasupporting
confidence: 55%
See 1 more Smart Citation
“…One retrospective, informatics-enabled study demonstrated that undergoing a surgical procedure was an independent risk factor for hospital-acquired hyponatremia [adjusted odds ratio (OR) 1.44, 95 % confidence interval (CI) 1.09-1.91]; this effect was similar to that attributed to fluid hypotonicity (adjusted OR 1.37, 95 % CI 1.03-1.84) [7]. A randomized controlled trial comparing 0.9 % saline and 0.18 % saline in a PICU population demonstrated that plasma sodium tended to decrease more in surgical patients than medical patients (-2.3 mmol/L; 95 % CI −0.46 to 0.1, P=0.057) [12].…”
Section: Postoperative Hyponatremiasupporting
confidence: 55%
“…Although the reported incidence of postoperative hyponatremia has varied from 11 to 31 % [6,8,9], nearly all studies consistently show that postoperative patients have an increased risk of developing hyponatremia [2,7,[10][11][12]. One retrospective, informatics-enabled study demonstrated that undergoing a surgical procedure was an independent risk factor for hospital-acquired hyponatremia [adjusted odds ratio (OR) 1.44, 95 % confidence interval (CI) 1.09-1.91]; this effect was similar to that attributed to fluid hypotonicity (adjusted OR 1.37, 95 % CI 1.03-1.84) [7].…”
Section: Postoperative Hyponatremiamentioning
confidence: 99%
“…Kannan, et al [13] have previously shown that hyponatremia is less common with the use of isotonic saline in standard volume (1.72%) as well as with reduced volume hypotonic saline solution (3.8%) when compared to standard volume hypotonic fluid (14.3%). Young and Keeley [14], however, reported that fluid type but not rate was significantly associated with hyponatremia in surgical pediatric patients.…”
Section: What This Study Adds?mentioning
confidence: 95%
“…Isotonic maintenance fluids have consistently been shown to lower the incidence of hyponatremia [6,[12][13][14][15][16]. Reducing the volume of administered fluid has also been shown to decrease the risk of hyponatremia in children with free-water excess [13].…”
Section: What This Study Adds?mentioning
confidence: 99%
“…It is now well established that hypotonic maintenance fluids result in hospital-acquired hyponatremia in children [8][9][10]. This has been best demonstrated in the post-operative setting where the incidence of hospital-acquired hyponatremia (sodium<135 mEq/L) is 20-30% [11][12][13][14][15]. Surprisingly, there have been no studies to evaluate the safety of the deficit-plus-maintenance-fluid approach in hospitalized children with gastroenteritis.…”
mentioning
confidence: 99%